특급호텔 종사원의 인구통계적 특성에 따른 인맥지수에 대한 탐색적 고찰 - 정효선; 윤혜현; Hyo Sun Jung; Hye Hyun Yoon (Journal of the Korean Society of Food Culture, 2015)
This study considered network quotient (NQ) of deluxe hotel employees and schematized characteristic attributes of being selected by employees with image through correspondence analysis in terms of cognition degree. Self-administrated questionnaires were completed by employees (292 samples) and data were analysed by frequency, t-test, one-way ANOVA, reliability and correspondence analysis. First, the hotel employees indicated the high average value in “participating in special education or seminar for improving ability (3.85±0.76). Second, as a result of analyzing difference according to gender, the average value in men was higher than in women. It was indicated that the higher age and career lead to a rise even in the average value of relationship index. Third, in consequence of carrying out correspondence analysis in order to prepare image map according to cognition level on relationship index in hotel employees, the measurement item that is placed in the closest distance to the response as saying of not so very was the response as saying of “having a lunch (dinner) engagement twice or three times a week.” On the other hand, the response as saying of “tending to have many acquaintances compared to coworkers” was schematized in the close distance to the response as saying of very so.